2019
DOI: 10.1186/s13104-019-4254-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, infection intensity and associated factors of soil transmitted helminths among primary school children in Gurage zone, South Central Ethiopia: a cross-sectional study design

Abstract: Objective The aim of this study was to determine the prevalence of soil transmitted helminthes among primary school children. School based cross-sectional study design was employed. A total of six hundred study subjects were selected by a multistage sampling method. Fresh stool specimens were collected using clean, dry and wide mouthed labeled stool cups. It was processed by Kato-Katz technique. The data were analyzed using SPSS version 20 and p-value < 0.05 was considered statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
11
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 17 publications
13
11
3
Order By: Relevance
“…The prevalence of any STH infection in Uba Debretsehay and Dara Mallo districts remain moderate endemic at the end of 2019 indicating elimination of morbidity target is failed in the area and needs continuation of annual deworming of SAC. The nding of this study was in agreement with Chuahit district [27] in Northern Ethiopia while it was higher than ndings of similar studies undertaken in Jima town [17] and Gurage Zone [16] in Ethiopia. In contrast to this, the prevalence of STH infection among SAC in the study area was lower than Hawassa town [18] and west Shewa Zone [22] in Ethiopia.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The prevalence of any STH infection in Uba Debretsehay and Dara Mallo districts remain moderate endemic at the end of 2019 indicating elimination of morbidity target is failed in the area and needs continuation of annual deworming of SAC. The nding of this study was in agreement with Chuahit district [27] in Northern Ethiopia while it was higher than ndings of similar studies undertaken in Jima town [17] and Gurage Zone [16] in Ethiopia. In contrast to this, the prevalence of STH infection among SAC in the study area was lower than Hawassa town [18] and west Shewa Zone [22] in Ethiopia.…”
Section: Discussionsupporting
confidence: 87%
“…Studies assessing the prevalence of STH and SCH infection revealed that it varied both spatially and temporally. Recent studies conducted in Ethiopia indicated that the prevalence of STH infection with different diagnostic technique ranged from 9.5% in Gurage Zone in South-central Ethiopia [16] to 52.4% in southwestern Ethiopia [17]. In Hawassa town, capital of SNNPR, the prevalence of any kind of intestinal parasitic infection was 42.4% [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All cases of STH infection were of low intensities, similar to ndings of study conducted in Gurage zone, Ethiopia (21). Low intensity infections is expected in areas with less than 20% prevalence of STH (3).…”
Section: Discussionsupporting
confidence: 79%
“…The sample size, 525 PSAC was determined using the formula for single population proportion (21) and considering 30% Prevalence of STH in the population (22), normal deviate of 1.96, 95% Con dence interval, 5% Margin of error, 10% non-response rate and design effect of 1.5.…”
Section: Study Areamentioning
confidence: 99%